Bibliometric Analysis: Research Trends in Project Based Learning Learning Models on Science Lesson Content (2003-2023) - Fitri, Intan Andhika; Sumarti, Sri Susilogati; Mulyono, Sungkowo Edy (Jurnal Penelitian Pendidikan IPA, 2023)
The project-based learning model is a learning model that is often used in the science learning process, especially in the independent curriculum, which prioritizes the learning process over cognitive outcomes. The purpose of this research is to find out research trends that apply project-based learning models to natural science content over a period of twenty years (2003–2023). The method used in this study is bibliometric analysis based on Scopus and Google Scholar publication data accessed through the Publish or Perish (PoP) application. The results of the bibliometric analysis were then visualized using the Vosviwer application. There are 33 publications on Scopus and a maximum data limit of 500 on Google Scholar in the period 2003–2023. Based on these findings, it can be seen that for the past 20 years, research on the application of the project-based learning model has often been carried out and follows the development of scientific knowledge.